2020
DOI: 10.1007/s11229-020-02549-8
|View full text |Cite
|
Sign up to set email alerts
|

Motivated ignorance, rationality, and democratic politics

Abstract: When the costs of acquiring knowledge outweigh the benefits of possessing it, ignorance is rational. In this paper I clarify and explore a related but more neglected phenomenon: cases in which ignorance is motivated by the anticipated costs of possessing knowledge, not acquiring it. The paper has four aims. First, I describe the psychological and social factors underlying this phenomenon of motivated ignorance. Second, I describe those conditions in which it is instrumentally rational. Third, I draw on evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 41 publications
1
61
0
2
Order By: Relevance
“…Do these many doubts contaminate the perception of the public and cause vaccine hesitancy? That is a known unknown: the publicization of a given issue on media channels does not necessarily amount to persuasion nor behavior change, but it may result in cognitive fatigue, misinformation, and polarization [1][2][3] , which are undesirable as well, given the extent of the crisis.…”
mentioning
confidence: 99%
“…Do these many doubts contaminate the perception of the public and cause vaccine hesitancy? That is a known unknown: the publicization of a given issue on media channels does not necessarily amount to persuasion nor behavior change, but it may result in cognitive fatigue, misinformation, and polarization [1][2][3] , which are undesirable as well, given the extent of the crisis.…”
mentioning
confidence: 99%
“…But there are plausible reasons to think this may not be voters' primary motivation for forming their policy preferences. Like others (Downs 1957), advocates of this view note that, for most policy issues, the opinions and behavior of any individual voter have negligible effect on the realization of policy outcomes (Kahan 2016;Williams 2019Williams , 2020. Thus, they argue that individual voters have negligible motivation to be sensitive to policy outcomes when forming their policy opinions.…”
Section: Discussionmentioning
confidence: 97%
“…However, studies on media framing have demonstrated it to not yield strong lasting results in the public as expected due to many other cognition processes related to self-perception, perception of others and expectation to belong to preferred groups and identities [45][46][47][48][49][50][51][52][53][54], as groups, their ideologies and identities, provide their own heuristics for perceiving and interpreting reality [55].…”
Section: The Appeal Of Spin and Media Frames To Scientists And Journalistsa Recipe For Misinformationmentioning
confidence: 99%
“…They organize the story, taking into account organizational and modality constraints, professional judgments and some judgments about the audience [41][42][43][44]. In contrast, people's information processing and their interpretation of facts and reality are also influenced by pre-existing structures, schemes of interpretation that end up interacting and determining how the news will be perceived, accepted, rejected, doubted, which aspects will be cherry-picked and to what extent for the purpose of ego enhancement, affirming identity and ideology, and belonging to groups [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]. That said, spin on research findings, spin in media coverage and news coverage frames are a recipe for completely losing control over any scientific narrative, laying grounds for misinformation, disinformation and all in-between.…”
Section: The Appeal Of Spin and Media Frames To Scientists And Journalistsa Recipe For Misinformationmentioning
confidence: 99%
See 1 more Smart Citation